(untitled) (TSUL LEGAL REPORT, 2026)
This article describes the concept of corruption and its content, various scientific and theoretical views on corruption, as well as the possible causes and consequences of corruption. They also discussed in detail the large-scale legal reforms aimed at preventing corruption in the country, state anti-corruption programs and mechanisms for their implementation, as well as best practices in combating corruption in developed countries. The author of the article emphasizes the importance of building immunity in the fight against corruption in the life of society in the Republic of Uzbekistan, and makes recommendations for the prevention of corruption based on the analysis of reforms and government programs in this area.